El Manejo De Los Desechos Hospitalarios Y Los Riesgos Laborales – Ambientales En El Hospital De Daule Área 16 “Dr. Vicente Pino Moran”. - Dominguez Bernita, Eva (2015)
In Ecuador aims to improve the health status of the population, which at present has developed the management of hospital waste and workplace hazards - Environmental hospital Daule area 16 "Dr. Pino Vicente Moran". That is why this research is to analyze the comprehensive management of hospital waste and the creation of a situational hygiene plan for the integrated management of waste generated in this health center action programs to reduce accidents labor. Since these wastes cause numerous accidents, especially puncture and thus, though not in all cases, transmission of serious diseases. Epidemiological studies of the World Health Organization WHO (2008) and Pan American Health Organization WHO (2010) in different countries worldwide with regard to infectious waste has been directly responsible for HIV transmission agent that causes AIDS and even the virus most frequently transmitted by the BOC hepatitis through injuries from needles or sharp objects. That is why for the United States, Chile and Canada greater emphasis on hospital waste management is given, considering that their legislation is reflected in the environmental law. The group that is more exposed to infectious risk are workers in health centers, handlers directly debris, mostly cleaning staff, by reviewing related literature it is evident that in developing countries, the available information about the risks of working in the hospital waste management is scarce or nonexistent.